Uji Efektivitas Pseudomonas fluorescens Dan Khamir Dalam Menghambat Penyakit Busuk Umbi Serta Memacu Pertumbuhan Tanaman Bawang Merah (Allium ascalonicum) - Hotim Hotim; Salamiah Salamiah; Gusti Rusmayadi (EnviroScienteae, 2020)
The main problem in the cultivation of shallots in South Kalimantan is rot diseases caused by Fusarium oxysporum. In South Kalimantan, until the present, this disease control is still not effective and efficient yet. One of the control techniques offered is the use of antagonistic agents because they are environmentally friendly. The study was carried out at the Plant Pest Laboratory in Sungai Tabuk District and the Bumimas Farmer Group's land in Upau District, Tabalong Regency, South Kalimantan. The study was carried out in two stages: 1. in vitro test was to see the effectiveness of using Pseudomonas fluorescens and Yeast in suppressing Fusarium oxysporum; 2. in vivo test to assess the effectiveness of P. fluorescens and Yeast in controlling F. oxysporum in the shallots field. The results showed that the application of P. fluorescens and Yeast was able to inhibit the growth of F. oxysporumin vitro, 64.03%, and 62.6%, respectively. The application of P. fluorescens was able to inhibit F. oxysporum bulb rot disease in Bima Brebes variety of shallots by 6.7% and could stimulate the number of roots in the field while the Yeast application effectively inhibited F. oxysporumbulb rot disease by 18.6%, and able to stimulate plant growth. The combination of P. fluorescens and Yeast is also effective in inhibiting F. oxysporum root rot by 20.3% and effective in stimulating the growth of onion plants in the field.